1976
DOI: 10.1080/00288330.1976.9515654
|View full text |Cite
|
Sign up to set email alerts
|

Factors controlling the entrance cross‐sectional areas of four inlets (note)

Abstract: The frequent occurrence of swell in the entrance to Wellington, Lyttelton, and Akaroa Harbours, coupled with the small littoral drift of sediment on adjacent rocky coastlines, appears to promote development of larger entrances than those associated with tidal control in unconsolidated sediment. In contrast to these three harbours, tidally controlled entrances have either bars or banks that protect them from severe swell and act as bypasses to the littoral drift of sediment.The entrance to Paterson Inlet lies o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

1977
1977
1992
1992

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(30 citation statements)
references
References 6 publications
0
30
0
Order By: Relevance
“…Interestingly, this took place at about the same time as comprehensive work on tidal inlet stability in United States inlets by Jarrett (1976), and drew comment by Mehta (1976) and comparison with United States inlets. In a follow-up paper based on further field data and examples, Heath (1976a) reported that the control on entrance dimensions was also dependent on the nature of the coast which determines the rate of supply of littoral drift to the entrance. The "FurkertHeath" relationship has probably been quoted and applied in every tidal inlet study since, and subsequently Hume & Herdendorf (1988b) warned of its shortcomings and suggested correct usage.…”
Section: Tidal Inletsmentioning
confidence: 99%
See 4 more Smart Citations
“…Interestingly, this took place at about the same time as comprehensive work on tidal inlet stability in United States inlets by Jarrett (1976), and drew comment by Mehta (1976) and comparison with United States inlets. In a follow-up paper based on further field data and examples, Heath (1976a) reported that the control on entrance dimensions was also dependent on the nature of the coast which determines the rate of supply of littoral drift to the entrance. The "FurkertHeath" relationship has probably been quoted and applied in every tidal inlet study since, and subsequently Hume & Herdendorf (1988b) warned of its shortcomings and suggested correct usage.…”
Section: Tidal Inletsmentioning
confidence: 99%
“…Thirdly, wide publicity surrounding beach erosion problems at Omaha (e.g., Schofield 1967;Beca Carter Hollings & Ferner Ltd 1976;Noble 1977;Healy 1981a) raised awareness of the interaction of tidal inlets with the adjacent beach and the possible detrimental effects of sand mining at an inlet Inlet stabilisation by groynes and beach nourishment was implemented after much debate, but not everyone agreed with the cause of the erosion nor the means of remedying the problem (Healy 1981a). Building on Furkert's work, Heath (1975) showed that for many inlets about the New Zealand coast the entrance cross-sectional area is linearly related to the tidal compartment (prism). This became known as the "Furkert-Heath" relationship, and was used to characterise inlets as being in states of equilibrium, deposition, or scour.…”
Section: Tidal Inletsmentioning
confidence: 99%
See 3 more Smart Citations